Impact of age and sex on neuroinflammation following SARS-CoV-2 infection in a murine model - Krishna, Venkatramana D.; Chang, Allison; Korthas, Holly; Var, Susanna R.; Seelig, Davis M.; Low, Walter C.; Li, Ling; Cheeran, Maxim C. -J. (Frontiers in Microbiology, 2024)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), the etiological agent of COVID-19, is known to infect people of all ages and both sexes. Senior populations have the greatest risk of severe COVID-19, and sexual dimorphism in clinical outcomes has been reported. Neurological symptoms are widely observed in COVID-19 patients, with many survivors exhibiting persistent neurological and cognitive impairment. The present study aims to investigate the impact of age and sex on the neuroinflammatory response to SARS-CoV-2 infection using a mouse model. Wild-type C57BL/6J mice were intranasally inoculated with SARS-CoV-2 lineage B.1.351, a variant known to infect mice. Older male mice exhibited a significantly greater weight loss and higher viral loads in the lung at 3 days post infection. Notably, no viral RNA was detected in the brains of infected mice. Nevertheless, expression of IL-6, TNF-α, and CCL-2 in the lung and brain increased with viral infection. RNA-seq transcriptomic analysis of brains showed that SARS-CoV-2 infection caused significant changes in gene expression profiles, implicating innate immunity, defense response to virus, and cerebrovascular and neuronal functions. These findings demonstrate that SARS-CoV-2 infection triggers a neuroinflammatory response, despite the lack of detectable virus in the brain. Aberrant activation of innate immune response, disruption of blood-brain barrier and endothelial cell integrity, and suppression of neuronal activity and axonogenesis underlie the impact of SARS-CoV-2 infection on the brain. Understanding the role of these affected pathways in SARS-CoV-2 pathogenesis helps identify appropriate points of therapeutic interventions to alleviate neurological dysfunction observed during COVID-19.